2019
DOI: 10.7150/jca.34944
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation biomarkers in stool for early screening of colorectal cancer

Abstract: Objective: Detection of aberrant methylated genes in feces has been developed as an early screening method for colorectal cancer. The aim of this study was to probe the methylation status of SEPT9, BMP3, NDRG4, and SDC2 in stool and study whether methylation of these genes is associated with colorectal cancer. Materials and Methods: DNAs were isolated and purified from cancerous and non-cancerous stool samples and colorectal cancer tissue. Gene methylation levels were quantified by methylation-specific PCR on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 33 publications
1
36
0
Order By: Relevance
“…Our earlier work on another blood based CRC screening assay, ColoDefense test that combines the detection of SEPT9 and SDC2 methylation in a single qPCR reaction, also improved the detection rates for early stage CRC and AA (Chen Y. et al, 2019;Zhao et al, 2019). To our knowledge, there has been only one published study examining the performance of methylated SEPT9 in combination with other methylation biomarkers on stool samples, and the AUC of methylated SEPT9 in that study was 0.815 (Chen J. et al, 2019). However, the performance of single methylated SEPT9 test on stool samples for each CRC stage and the performance comparison between stool methylated SEPT9 test and plasma methylated SEPT9 test have never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier work on another blood based CRC screening assay, ColoDefense test that combines the detection of SEPT9 and SDC2 methylation in a single qPCR reaction, also improved the detection rates for early stage CRC and AA (Chen Y. et al, 2019;Zhao et al, 2019). To our knowledge, there has been only one published study examining the performance of methylated SEPT9 in combination with other methylation biomarkers on stool samples, and the AUC of methylated SEPT9 in that study was 0.815 (Chen J. et al, 2019). However, the performance of single methylated SEPT9 test on stool samples for each CRC stage and the performance comparison between stool methylated SEPT9 test and plasma methylated SEPT9 test have never been reported.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA promoter present a global hyper-methylation character in colon cancer some studies have point out DNA methylation have potential role in early screening of colon cancer [31]. Here, we investigate the DNA methylation character in lncRNA promoter for colon cancer.…”
Section: Resultsmentioning
confidence: 95%
“…Alteration of DNA methylation has been implicated in tumor progression and disease development, and studies have identified a potential role for DNA methylation in early screening of colon cancer ( Chen et al, 2019 ). Here, we investigated DNA methylation in lncRNA promoters in colon cancer.…”
Section: Resultsmentioning
confidence: 99%